2020
DOI: 10.1155/2020/1827107
|View full text |Cite
|
Sign up to set email alerts
|

From Chance to Serendipity: Knowledge Workers’ Experiences of Serendipitous Social Encounters

Abstract: Serendipity refers to uncontrolled circumstances that lead to unexpected yet fortunate discoveries. The phenomenon has been studied extensively in relation to information retrieval. However, serendipity in the context of social encounters has been the subject of few empirical studies. In professional life, social serendipity might result in benefits such as fruitful collaboration, successful recruitment, discovery of novel information, and acquisition of crucial new perspectives from peers. Despite the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…For the creation stage social serendipity, the making of new, potentially beneficial acquaintances not encountered in the course of normal business activity, is valued and is considered to be relatively high at largescale networking events where mingling occurs. Social serendipity and serendipity more generally have been theorized in other fields such as management, communication, and computer studies (Olshannikova et al 2020). Björneborn (2017) has suggested three broad affordances of serendipity: (1) diversifiability, being able to encounter diverse contents;…”
Section: Networking Activities: Rapport Building and Social Serendipitymentioning
confidence: 99%
“…For the creation stage social serendipity, the making of new, potentially beneficial acquaintances not encountered in the course of normal business activity, is valued and is considered to be relatively high at largescale networking events where mingling occurs. Social serendipity and serendipity more generally have been theorized in other fields such as management, communication, and computer studies (Olshannikova et al 2020). Björneborn (2017) has suggested three broad affordances of serendipity: (1) diversifiability, being able to encounter diverse contents;…”
Section: Networking Activities: Rapport Building and Social Serendipitymentioning
confidence: 99%
“…Our work highlights this goal toward diversification and heterogeneity, especially in the professional networking context where diversity is seen as a key driver for fruitful collaboration [2]. Diversifying people recommendations can enable unexpected yet valuable social encounters [12], which require alternative recommendation strategies to identify relevant people in the vast and complex Twitter network. Traditional recommender systems research seeks to optimize algorithmic accuracy and effectiveness [13,14], creating algorithms that can reproduce actors' current behavior as accurately as possible [15] rather than aiming at increasing diversity.…”
Section: Introductionmentioning
confidence: 96%
“…Ge et al, 2017;Delva, Smets, Colpaert, Ballon, & Verborgh, 2020;Li & Tuzhilin, 2019;Shepard, 2011) or applications to connect strangers in public places (Paulos & Goodman, 2004). Research on serendipity has, however, demonstrated that serendipity evolves differently in different contexts inducing the need to further investigate serendipity in urban recommender systems in particular (Lutz, Pieter Hoffmann, & Meckel, 2017;Sun, Sharples, & Makri, 2011;Olshannikova, Olsson, Huhtamäki, Paasovaara, & Kärkkäinen, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These few examples include applications for urban navigation (Delva et al, 2020; Ge et al, 2017; Li & Tuzhilin, 2019; Shepard, 2011) or applications to connect strangers in public places (Paulos & Goodman, 2004). Research on serendipity has, however, demonstrated that serendipity evolves differently in different contexts inducing the need to further investigate serendipity in urban recommender systems in particular (Lutz et al, 2017; Olshannikova et al, 2020; Sun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%